Viral hepatitis B and C infections increase the risks of intrahepatic and extrahepatic cholangiocarcinoma: Evidence from a systematic review and meta-analysis - Tan, Jie-hui; Zhou, Wan-yan; Zhou, Lei; Cao, Rong-chang; Zhang, Guo-wei (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Previous study has shown a positive relationship between the hepatitis B virus (HBV) or hepatitis C virus (HCV) infection and cholangiocarcinoma (CCA); however, their correlation with different anatomical sites of CCA (i.e. ICC and ECC) has not been revealed. This study aims to evaluate the association of HBV or HCV infection with CCA, including the intrahepatic cholangiocarcinoma (ICC) and extrahepatic cholangiocarcinoma (ECC), and to determine the roles of α-1 fetoprotein (AFP), CA19-9, and lymph node involvement in CCA with HBV infection. Materials and Methods: Relevant studies published between 2004 and 2016 were systematically searched and retrieved from PubMed, SpringerLink, and Science Direct using key terms such as “cholangiocarcinoma”, “bile duct cancer”, “extrahepatic cholangiocarcinoma”, and “intrahepatic cholangiocarcinoma”. The demographic, clinical, and laboratory data were extracted from the included studies, and the meta-analysis was performed using RevMan and STATA 11.0 software. Results: A total of 13 studies with CCA matched the inclusion criteria in this meta-analysis, including 7,113 CCA patients and 24,763 controls. This meta-analysis showed that the HBV or HCV infections can significantly increase the risk of CCA, including ICC and ECC. In addition, the higher levels of AFP, lower levels of CA19-9, and lymph node involvement were detected in the CCA patients with HBV infection as compared to those without. Conclusion: The HBV and HCV infections significantly increased the risk of CCA, as well as ICC and ECC. The involvement of AFP, CA19-9, and lymph nodes may play an important role in the diagnosis of CCA.